The joy of eating : a guide to food in modern pop culture - Glenn, Jane K. (ABC-CLIO, 2022)
"This volume explores our cultural celebration of food, blending lobster festivals, politicians' roadside eats, reality show "chef showdowns," and gravity-defying cakes into a deeper exploration of why people find so much joy in eating"-- Provided by publisher.
Keywords: Food -- United States -- History.; Food habits -- Social aspects -- United States.; Food in popular culture -- United States.; Aliments -- États-Unis -- Histoire.; Habitudes alimentaires -- Aspect social -- États-Unis.; Aliments dans la culture populaire -- États-Unis.; SOCIAL SCIENCE / Agriculture & Food (see also POLITICAL SCIENCE / Public Policy / Agriculture & Food Policy); SOCIAL SCIENCE / Popular Culture.; Food; Food habits -- Social aspects; Food in popular culture; United States; History